Kemandirian Belajar Siswa pada Pembelajaran Daring selama Pandemi di SMA Cokroaminoto Sukaresmi - Hidayah, Siti Ismi Nurul; Kuntari, Septi (ANWARUL, 2022)
This study aims to describe the independence of students' learning during online learning which includes (1) behaving according to their own initiative, independence from others, level of self-discipline, and ability to solve their own problems; (2) the factors behind the formation of independent learning. This study uses a qualitative descriptive approach with the aim of understanding natural events in the research object whose research results are presented descriptively. The research was conducted at SMA Cokroaminoto Sukaresmi Kab, Cianjur with the research informants being teachers and students of class XI IPS at the school. The data collection techniques through interview techniques and literature study and to test the validity of the research data using data triangulation techniques. The results showed that the level of independence of students in online learning of sociology subjects was still low and the factors that formed the independence of learning sociology for class XI students of SMA Cokroaminoto tend to be influenced by external factors, namely school factors and family factors.